Interpretation of Term of Office by the KPU in Regional Elections: Analysis from the Perspective of Legal Interpretation and Legal Certainty - Evi Selviani; Nur Annisa Putri; Elmiati Nurdin; Nur Ilmi Putri Febriyanti; Erni Yoesry (International Journal of Business, Law, and Education, 2026)
The interpretation of the term of office of Regional Heads has become a crucial issue in the implementation of Regional Head Elections (Pilkada) in Indonesia, particularly when there is a discrepancy in the methods used by the General Election Commission (KPU) and the Contitutional Court (MK) in interpreting the term of office. In practice, the Constitutional Court adopt a combination of systematic, teleological, and historical interpretative approaches, which consider the substantive meaning of the term of office and the purpose of limiting power. Conversely, the KPU tends to employ a grammatical approach that emphasizes methodologies but also has serious implications for legal certainty, electoral legitimacy, citizens political right, and the credibility election results. The study aims to analyze the construction of legal interpretations regarding the term of office from the perspectives of the KPU and MK and its implications for the conduct of Pilkada. The method used is a normative juridical approach through a literature review of legislation, MK decisions, and legal literature. The results of the study indicate that a lack of harmonization in interpretation has the potential to create legal anda administrative conflicts and opens the door to abuse of power. Therefore, harmonization of interpretation is necessary through regulations based on constitutional principles to ensure fair, democratic elections that uphold legal certainty.